Purpose and Providence in Evolutionary Perspective: Considerations for Theological Anthropology in Light of Biocultural Evolution and Genetic Engineering - Burdett, Michael S. (Heythrop journal, 2025)
We argue here that bringing insights from evolution and bioengineering to bear on traditional accounts of divine providence helps to illustrate just how complex providence is and how difficult it is to achieve. While other non-human animals might exhibit greater agency in creation and its evolutionary development than has traditionally been recognised, we contend non-human animals don't meet the threshold for acting providentially. However, the interplay between biological and cultural evolution prior to the arrival of modern human beings gives us a fresh perspective on God's providence through these intermediate forms that are much more interlinked than previously afforded. When considering the human being, the complexity and difficulty of achieving genuine providence is even more acute. Here human beings bear the potential to act providentially by having the capacities for foresight, benevolence, and power, but are still limited in exercising each of these in specific instances—often failing owing to weakness or deliberate intention. Human power to influence or create existing and new creaturely and evolutionary trajectories through substantial cultural production and bioengineering should be met with great humility, sobriety, and prudence, because our foresight and benevolence are profoundly limited.